Flux of cadmium through a laboratory food chain (media-algae-mussel) and its effects - Hennig, Helmke F-K O (Department of Chemistry, 2015)
The increasing pollution of the aquatic environment by cadmium is a potentially severe problem and techniques are needed to document the effect of the metal. To investigate the flux of this metal through a laboratory food chain, algae were grown in various cadmium concentrations for subsequent use as contaminated food for mussels. The results showed that in order to make valid deductions, more information about chemical mechanisms and background ecophysiological data is needed, otherwise accumulation reports may become misleading. It was found that the best growth and accumulation results were achieved by harvesting algae from a zinc deficient media containing 7 Î¼mole dm-3 cadmium and at a particular life cycle phase. Two uptake mechanisms are proposed. These "contaminated" algae were fed to mussels under different accumulation regimes. The metal gain and loss were determined and compared to a "baseline" dry body weight which had been calculated from a shell length-body weight relationship. Cadmium accumulation took place in the mussels and after some initial delay, could be correlated to weight loss. Such a weight loss was due to pathological and biochemical changes in the mussels. It was shown that the toxic effect of cadmium could be determined much earlier by the presence of special proteins. The elutant profiles of the gel chromatography study showed the production of metal binding protein as well as a spill over of cadmium into the enzyme pool, caused by a higher uptake than elimination rate. Cadmium on metal binding protein and in the enzyme pool could be related to the poisoning effect of the metal and a pollution history for the mussels identified. The characteristics of the metal binding protein were found to be very similar to those reported for metallothionein and had an approximate molecular weight of 10 600 daltons.